Keep Your Mentee Disappointed - Gil Eyal (Sociologica)
Commenting on a Talmudic expression, that exhorts one to “make for thyself a Rabbi”, I suggest that the mentoring relationship involves the student making an emotional investment and constructing an (often distorted) image of their mentor as possessing superior mastery. I argue that this process cannot be understood with our model of liberal education, because being mentored as a sociologist involves learning a craft, and is akin to the ancient cultural model of apprenticeship. I conclude with some thoughts about the ethical duty of the mentor that this model entails, the most important of which is to disappoint your mentee in the right measure and at the right time.